Avian Influenza A (H5N1) : Patogenesis, Pencegahan Dan Penyebaran Pada Manusia - Radji, Maksum (Majalah Ilmu Kefarmasian, 2006)
Avian influenza A (H5N1), or highly pathogenic avian influenza (HPAI), has become the worldÂ’s attention because of possibility of global pandemic. This review describes the features of human infection, pathogenesis, transmission, and clinical management of avian influenza A (H5N1).